Imprensa maranhense no início do século XIX: uma análise dos discursos sobre a escravização no jornal Conciliador do Maranhão (1821 -1823) - Barros, Leonardo Barborsa (2023)
This research aims to reflect on the discourses about enslavement in the pages of the newspaper O Conciliador do Maranhão, in São Luís (MA). Founded in 1821, the journal was the first in the province of Maranhão. To carry out this study, documents scanned on the website of the Hemeroteca Digital Nacional were used. In all, 212 editions circulated, but for the preparation of the dissertation, 57 were selected. This amount was chosen from the mentions on the subject of slavery. The objective is to analyze the discourses on enslavement, between 1821 and 1823, the period in which it circulated, seeking to understand the social aspects in which the enslaved lived, the forms of resistance they used, identifying the profile of the captives. It is also the purpose of this study to analyze how the enslaved were seen by society in Maranhão, through advertisements for sales, auctions and escapes published by the masters. Letters, news, notices and letters from readers that address the issue of enslavement will also be analyzed. From there, it is possible to profile the enslaved people who appear in the newspaper and identify the political and economic interests on the subject. Methodologically, Discourse Analysis (DA) is used with the intention of understanding the social and power relations in the hegemonic discourses present in the news, as well as making a debate about the importance of the press as a source of historical research and knowing more about the its relevance in Maranhão society at the beginning of the 19th century. It is noticed that the newspaper is in line with the speeches of the local elites, as it defends the maintenance of the enslavement of black people. In advertisements for the sale of slaves, the newspaper reinforces the idea of treating these people as objects that could be sold or bought, the ideal type of slave for masters, as well as the professions most sought after by them. In the escape advertisements, slave resistance is noted, showing that these people did not passively accept such a condition. It is also observed the dependence of the masters on slave labor, through the advertisements used as a way to recover the fugitive captive.